Task Analysis on Workbook Entitled "Satria" for Junior High School Used in Klaten Regency Based on The Criteria of GoodTask Suggested by Chandlin (1987) - Rahayu, Didi Sri (2012)
This study aims at analyzing the tasks provided in the workbook entitled "Satria" used in Klaten Regency based on the criteria of good tasks suggested by Candlin (1987), then the study aims at finding the criteria of good tasks based on the criteria of good tasks suggested by Candlin (1987) and those that are not found in tasks provided in the workbook entitled "Satria" used in Klaten Regency This type of this research is descriptive qualitative reserch. The method of collecting data is comparing method and analyzing document by selecting tasks on the workbook entitled "Satria" for Junior High School used in Klaten Regency that fulfill with the criteria of good tasks suggested by Candlin. The results of the study show that there are 18 criteria that are appropriate with the criteria of tasks and there are tasks in the workbook that do not fulfill 2 criteria by Candlin. The tasks in the workbook for Junior High School used in Klaten Regency are categorized as very good tasks because from 20 criteria by Candlin, there are 18 criteria that fulfill the tasks in the workbook and then just 2 criteria that do not fulfill the tasks on workbook for Junior High School Used in Klaten Regency